Elastic and mechanical properties of aluminium and silicon carbide using density functional theory and beyond. (August 2021) - Barhoumi, M.; Sfina, N.; Said, M.; Znaidia, S.
Abstract: For a long time and until now, there is still a lack of theoretical and experimental data on the third-order elastic constants, which limits the chance of producing new materials with targeted mechanical responses. For this purpose, we went back to the sixties (i.e., the year 1960 and after) to understand and improve these constants because they play a highly significant role in engineering. Applying density functional theory and for the first time with the adiabatic-connection fluctuation–dissipation theorem in the random phase approximation, we study the electronic, elastic, and mechanical properties of aluminium and silicon carbide. Our second-order elastic constants predictions give an extraordinary agreement with experimental data. In this framework, we investigate the mechanical properties such as Young's modulus, Poisson's ratio, bulk modulus, and shear modulus of diamond and silicon structures. Also, we visualize the three-dimensional plot, as well as two-dimensional for Young's modulus, and others. For the third-order elastic constants, we show that we can be used our random phase approximation results as a reference to the place of experimental values. Highlights: We study the elastic and mechanical properties of aluminium and silicon carbide. Our SOECs predictions give an extraordinary agreement with experimental data. We visualize the 3D plot, as well as 2D for Young's modulus. For TOECs, we can be used our RPA results as a reference to the place of experimental values.